2021
DOI: 10.1371/journal.pone.0253254
|View full text |Cite
|
Sign up to set email alerts
|

Influence of collagen and some proteins on gel properties of jellyfish gelatin

Abstract: Marine gelatin is one of the food proteins used in food and non-food products, offering desirable functionalities such as gelling, thickening, and binding. Jellyfish has been chosen for this gelatin research, in view of the benefits of its main collagen protein and lower fat content, which may reduce the amounts of chemicals used in the preparative steps of gelatin production. To date, the lack of identified proteins in gelatin has limited the understanding of differentiating intrinsic factors quantitatively a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 35 publications
1
29
1
Order By: Relevance
“…Based on analysis of variance (ANOVA) shows that Fhit>Ftab means that the addition of fish scale collagen extract has a significant effect on the dispersion value. This is in accordance with the statement of [16] collagen has thickening properties. Collagen mixed into ointment preparations as an active substance can affect the ointment base itself, so that the spreadability is lower.…”
Section: Spreadability Ointmentsupporting
confidence: 93%
“…Based on analysis of variance (ANOVA) shows that Fhit>Ftab means that the addition of fish scale collagen extract has a significant effect on the dispersion value. This is in accordance with the statement of [16] collagen has thickening properties. Collagen mixed into ointment preparations as an active substance can affect the ointment base itself, so that the spreadability is lower.…”
Section: Spreadability Ointmentsupporting
confidence: 93%
“…For gelatin extraction, jellyfish by-products gelatin was prepared according to Lueyot et al [11] and Charoenchokpanich et al [12] with a slight modification. Firstly, the desalted by-products (1 kg) were agitated at 150 rpm and 4 o C for 2 h with 0.5 M sodium hydroxide (NaOH) solution (1:3, w/v) in a shaking incubator (WIS-20R, WiseCube, Korea).…”
Section: Preparation Of Jellyfish By-products Gelatinmentioning
confidence: 99%
“…However, the gel strength of commercial fish gelatin (306.11 g) was lower than that of the JFG48 sample. Previous research has found that jellyfish by-products gelatin has lower gel strength due to differences in collagen type, the alpha and beta chain ratio in the gelatin, and the gelatin peptides of the alpha chain [11]. The lowest gel strength of jellyfish (Lobonema smithii) gelatin was 108.36 g [15].…”
Section: Gel Strengthmentioning
confidence: 99%
See 2 more Smart Citations